CHILDHOOD EXPERIENCES IN LATE MODERNITY : REFLECTIONS FROM “NOBODY KNOWS" - Kielb, Eliziane Gorete; Silva, Ivone Maria Mendes (Literatura em Debate, 2025)
This study aimed to problematize, based on the analysis of the film “Nobody Knows”, how the ways of experiencing childhood and constituting the child subject through social relations have been marked, in contemporary times, by experiences such as symbolic orphanhood, helplessness, forced protagonism, among others that have become distinctive features of late modernity, according to studies from fields such as Childhood Sociology, Psychoanalysis, and Cultural Studies. The analyzed film narrative was approached as a historical document, that is, understood as part of a socio-historical context with which it dialogues and to which attention must be directed in order to comprehend it. The results revealed a heterogeneity of experiences lived by children in public life, at school, with their families and peers, indicating ongoing social transformations that need to be better understood in their causes and repercussions. There is a need to (re)think conceptions of childhood, education, and care, considering multiple cultural, social, and historical singularities. To better meet children’s needs, according to the analysis presented here, the ideal is to establish a balance between the protection provided by adults and the active participation of children in their own experiences, promoting their autonomy without neglecting the necessary support.